Quantification of gear inflicted damages on trawl-caught haddock in the Northeast Atlantic fishery - Sistiaga, Manu; Herrmann, Bent; Brinkhof, Jesse; Larsen, Roger B.; Jacques, Nadine; Santos, Juan; Gjøsund, Svein Helge (Marine Pollution Bulletin, 2020)
External damages are indicators of the overall quality of fish and fish welfare. Haddock is an important commercial species widespread in the North Atlantic, but few studies related to quality have been carried out on this species. We studied the levels of external damages on haddock captured with a demersal trawl in the Northeast Atlantic. Further, we investigated to what extent the compulsory sorting grid and diamond mesh codend gear configuration employed in this trawl fishery is responsible for the external damages observed during the capture process. We evaluated external damages on 563 haddock captured over 22 hauls. In general, the results showed that catching haddock without any gear inflicted damages using demersal trawls is challenging. However, the results also showed that the severity of most damages is low and the probability to catch haddock with no external damage can be significantly increased removing the grid and changing codend design.